Discovery of 2-aminoisobutyric acid ethyl ester (AIBEE) phosphoramidate prodrugs for delivering nucleoside HCV NS5B polymerase inhibitors. Issue 7 (1st April 2020) - Randolph, John T.; Li, Tongmei; Chris Krueger, A.; Heyman, Howard R.; Chen, Hui-Ju; Bow, Daniel A.J.; Van Handel, Cecilia; Peterkin, Vincent; Carr, Robert A.; Stolarik, DeAnne; Dekhtyar, Tatyana; Irvin, Michelle; et al.
Graphical abstract: Abstract: Our HCV research program investigated novel 2′-dihalogenated nucleoside HCV polymerase inhibitors and identified compound 1, a 5′-phosphoramidate prodrug of 2′-deoxy-2′-α-bromo-β-chloro uridine. Although 1 had a favorable in vitro activity profile in HCV replicons, oral dosing in dog resulted in low levels of the active 5′-triphosphate (TP) in liver. Metabolism studies using human hepatocytes provided a simple assay for screening alternative phosphoramidate prodrug analogs. Compounds that produced high TP concentrations in hepatocytes were tested in dog liver biopsy studies. This method identified 2-aminoisobutyric acid ethyl ester (AIBEE) phosphoramidate prodrug 14, which provided 100-fold higher TP concentrations in dog liver in comparison to 1 (4 and 24 h after 5 mg/kg oral dose).